Ethnobotanical knowledge among the semi-pastoral Gujjar tribe in the high altitude (Adhwari's) of Churah subdivision, district Chamba, Western Himalaya - Dipika Rana; Anupam Bhatt; Brij Lal (BMC, 2019)
Abstract Background The wild plants not only form an integral part of the culture and traditions of the Himalayan tribal communities but also contribute largely to the sustenance of these communities. The tribal people use large varieties of wild fruits, vegetables, fodder, medicinal plants, etc. for meeting their day-to-day requirements. The present study was conducted in Churah subdivision of district Chamba where large populations of Muslim Gujjars inhabit various remote villages. These tribal people are semi-pastoralists, and they seasonally (early summers) migrate to the upper altitudes (Adhwari's) along with their cattle and return to permanent settlements before the onset of winters. A major source of subsistence of these tribal people is on natural resources to a wide extent, and thus, they have wide ethnobotanical knowledge. Therefore, the current study was aimed to report the ethnobotanical knowledge of plants among the Gujjar tribe in Churah subdivision of district Chamba, Himachal Pradesh. Methods Extensive field surveys were conducted in 15 remote villages dominant in Gujjar population from June 2016 to September 2017. The Gujjars of the area having ethnobotanical knowledge of the plants were interrogated especially during their stay at the higher altitudes (Adhwari's) through well-structured questionnaires, interviews, and group meetings. The data generated was examined using quantitative tools such as use value, fidelity, and informant consensus factor (F ic). Results This study reveals 83 plants belonging to 75 genera and 49 families that were observed to have ethnobotanical uses. Plants were listed in five categories as per their use by the Gujjars, i.e. food plants, fruit plants, fodder plants, household, and ethnomedicinal plants. The leaves, fruits, and roots were the most commonly used plant parts in the various preparations. The highest number of plants was recorded from the family Rosaceae followed by Polygonaceae and Betulaceae. On the basis of use value (UV), the most important plants in the study area were Pteridium aquilinum, Juglans regia, Corylus jacquemontii, Urtica dioica, Diplazium maximum, and Angelica glauca. Maximum plant species (32) were reported for ethnomedicinal uses followed by food plants (22 species), household purposes (16 species), edible fruits (15 species), and as fodder plants (14 species). The agreement of the informants conceded the most from the use of various plants used as food plants and fruit plants (F ic = 0.99), followed by fodder plants and household uses (F ic = 0.98) while it was least for the use of plants in ethnomedicine (F ic = 0.97). The fidelity value varied from 8 to 100% in all the use categories. Phytolacca acinosa (100%), Stellaria media (100%), and Urtica dioica (100%) were among the species with high fidelity level used as food plants, while the important species used as fruit plants in the study area were Berberis lycium (100%), Prunus armeniaca (100%), and Rubus ellipticus (100%). Some important fodder plants with high fidelity values (100%) were Acer caesium, Aesculus indica, Ailanthus altissima, and Quercus semecarpifolia. The comparison of age interval with the number of plant use revealed the obvious transfer of traditional knowledge among the younger generation, but it was mostly concentrated in the informants within the age group of 60-79 years. Conclusions Value addition and product development of wild fruit plants can provide an alternate source of livelihood for the rural people. The identification of the active components of the plants used by the people may provide some useful leads for the development of new drugs which can help in the well-being of mankind. Thus, bioprospection, phytochemical profiling, and evaluation of economically viable products can lead to the optimum harnessing of Himalayan bioresources in this region.